DUET THIS: STORYTELLING THROUGH SOCIAL MEDIA VIDEO FOR TEACHING ENGLISH - Damayanti, Ika Lestari; Nurlaelawati, Iyen; Amalia, Lulu Laela; Dharma, Nindya Soraya; Ratnaningsih, Sri (English Review: Journal of English Education, 2023)
This case study aimed to investigate the use of the social media video application, TikTok, to support ten EFL teachers in Indonesia to develop videos for storytelling with their students. During the emergency remote teaching, these teachers found difficulty in designing learning materials easy to share on various online platforms. In this study, a two-week training program consisting of face-to-face and online sessions was conducted to facilitate the teachers to explore TikTok affordances and tell stories in the form of TikTok’s Duet. The data were collected from TikTok videos produced during the program and the teachers’ pre- and post-training reflective notes. The findings show the teachers’ shifted view of TikTok as non-educational entertainment to an educational platform that could facilitate interactive and interesting storytelling with students. The teachers were aware that while the short duration of the TikTok video was beneficial for easy sharing and engagement with students, it affected the length of the unfolding stages of the story. In creating a TikTok video for storytelling, the teachers found modifying original stories into a one-minute interactive video challenging. More support is thus required to provide teachers with pedagogical, technological, and language content knowledge that allows them to develop teaching resources relevant to their student’s language learning needs and social and economic backgrounds.